2012
DOI: 10.1186/1746-6148-8-134
|View full text |Cite
|
Sign up to set email alerts
|

Sub-clinical mastitis and associated risk factors on lactating cows in the Savannah Region of Nigeria

Abstract: BackgroundSub-clinical mastitis limits milk production and represents an important barrier to profitable livestock economics worldwide. Milk production from cows in Nigeria is not at optimum levels in view of many factors including sub-clinical mastitis.ResultsThe overall herd-level prevalence rate for SCM was 85.33% (256/300 heads of cows) while the quarter-level prevalence rate of SCM was 43.25% (519/1,200 quarters). The prevalence of SCM was 50.67%, 43.67%, 39.67% and 39.13% for the left fore-quarter, right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 19 publications
8
34
6
1
Order By: Relevance
“…Age wise the present study indicate significantly (P <0.05) higher CPS infection at advanced age which is in agreement with the finding of Rigbe Haftu et al, (2012). This is probably due to prolonged period of exposure to the infecting organisms and predisposing factors like stress of lactation which favor dilation of teat canal due to repeat milking thereby facilitating the entry of pathogens into the teat canal to cause subclinical intramammary infection (Shittu et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Age wise the present study indicate significantly (P <0.05) higher CPS infection at advanced age which is in agreement with the finding of Rigbe Haftu et al, (2012). This is probably due to prolonged period of exposure to the infecting organisms and predisposing factors like stress of lactation which favor dilation of teat canal due to repeat milking thereby facilitating the entry of pathogens into the teat canal to cause subclinical intramammary infection (Shittu et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…This is comparable with the reports of Ameh et al (1999), but differ with the 44.9% and 43.25% overall quarter prevalence reported by Mekibib et al (2010) and Shittu et al (2012) in Holeta town, Central Ethiopia and Savannah region of Nigeria respectively. The traditional method and protocol of milking cows was the method practiced in all the herds sampled, thus milking hygiene was generally poor in the majority of the farms sampled.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of clinical mastitis at cow level was 26.9% (n=97) (Table 1), the prevalence of subclinical mastitis as detected by CMT was 23.9% while that of the clinical mastitis is 3.1% (Table 1). The prevalence in the present study is lower than the 52% reported by Junaidu et al (2011) in Sokoto, Nigeria, 85.33% by Shittu et al (2012) in the Savannah region of Nigeria, 30.9% by Suleiman et al (2013) in Plateau Sate, Nigeria and 71.0% by Mekibib et al (2010) in Ethiopia.…”
Section: Discussioncontrasting
confidence: 79%
“…The high prevalence of the disease in older animals related to the physiology of threat canal which is more dilated and remains partially open due to years of repeated milking. This facilitates the entrance of environmental and skin-associated microorganisms leading clinical or sub clinical mastitis [3,18]. Blowey & Edmondson [4] also reported the high occurrence of mastitis in older aged cows compared to young and adult cattle.…”
Section: C) Agementioning
confidence: 99%